Methods in microbiology. - Norris, J. R. (John Robert); Read, D. J. (David J.); Varma, A. K. (Methods in microbiology, 1992)
Volumes 23 and 24 of this highly acclaimed series focus on methods used for the study of both ectomycorrhiza and vesicular-arbuscular mycorrhiza. Written by a team of international experts, these volumes comprise the most extensive compilation of methods available on this topic.